Combining antimicrobial photodynamic therapy with curcumin and with methylene blue against S. mutans - Hariyani, Ninuk; Setyowati, Dini; Armadanty, Talsha Irzaputri; Amiati, Devy Ratriana; Dani, Anugrah Putra; Shoaib, Lily Azura; Shanbhag, Namita (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
ntimicrobial photodynamic treatment (aPDT) is a treatment method that links a light source to a photosensitizing carrier. There is no clear standardization regarding the exact therapeutic concentration when it is combined with curcumin or methylene blue, and there is no comparison of their activities toward S. mutans. We aimed to assess the best composition of the combination of aPDT and curcumin and with the combination of aPDT and methylene blue in reducing the number of S. mutans biofilms. The searches were carried out in Pubmed, ScienceDirect, and Proquest from 2015 to April 2023; collecting in-vitro and in-vivo research. Two authors independently reviewed studies, assessed their quality and eligibility, then extracted the data. 14 articles that met the inclusion criteria were retained. The final results were then grouped into 2, showing the effectiveness for a combination of aPDT and methylene blue and of aPDT and cucumin (9 and 5 articles, respectively). Each combination has different aPDT properties. The combination of aPDT and methylene blue is effective in reducing S. mutant biofilm in 660 nm diode laser wavelength and 40 mW output power. Furthermore, aPDT combined with curcumin is effective in reducing S. mutants biofilm in a wavelength of 405 nm and an irradiation time of 50-150 seconds. The addition of EDTA in a combination of aPDT and curcumin could increase its effectivity.